Optimalisasi Keuntungan Kantin Kampus Dengan Program Linear Menggunakan Metode Simpleks: (Studi Kasus: Kantin Pondok Bitung) - Chresensi Aghel Birana; Grezika Liling Taruk Allo; Keiko P. Tendeno Runtukahu; Prily Azizah Humu; Vemelia Esterlita Daud; Voni Tiku Rede; James U. L. Mangobi (SOSCIED, 2025)
To improve the profitability of food production within the Pondok Bitung Canteen case study, this study uses linear programming methodology, specifically the simplex method, to examine the role and contribution of Micro, Small, and Medium Enterprises (MSMEs) to the Indonesian economy. This study employs a quantitative approach, with interviews as the primary method of data collection. The collected data will be analyzed using triangulation techniques and an interactive analysis framework. Despite the challenges faced by businesses in gaining access to international supply chains, the study demonstrates that MSMEs are crucial for increasing PDB and creating jobs. Furthermore, the application of the simplex method demonstrates that Pondok Bitung Canteen can maximize profits by determining the optimal production volume for two main dishes, namely fish and chicken, based on the limited raw materials available. This investigation is crucial for benefiting MSME stakeholders, developers, and scholars, as well as assisting Pondok Bitung Canteen in improving the efficiency and effectiveness of its food production process.